Influence of successive bean plantings on the severity of angular leaf spot and rust and yield losses - Rodrigues, Fabrício de Ávila; Fernandes, Jonas Jager; Martins, Maurício (Pesquisa Agropecuaria Brasileira, 1999)
Angular leaf spot (Phaeoisariopsis griseola) and rust (Uromyces appendiculatus) are some of the most damaging bean diseases in the region of Triângulo Mineiro, State of Minas Gerais, Brazil. The experiments were conducted under field conditions during the 1994 dry season (under sprinkler irrigation) and 1994/95 rainy season, with three bean planting dates in each season. The purpose of this study was to determine the influence of these sequential plantings on the severity of angular leaf spot and rust in field beans, as well as the yield reduction caused by these diseases. The severity of angular leaf spot and rust increased significantly from the first to the third planting time and reached the highest severity in the third. Previous bean cultivation were the source of inoculum for the subsequent plantings. Fungicide applications were efficient in controlling both diseases. Bean grain yield was significantly higher when fungicide was used compared to the untreated control. Angular leaf spot showed the highest severity in both dry and rainy season. The rust, only in the 1994 in the dry season. The seasons showed climatic conditions (temperature and relative humidity) more favorable for diseases evolution, resulting in increase of severity. A negative and highly significant correlation was observed between the severity of angular leaf spot and rust with the grain yield in the two seasons.
Keywords: Phaseolus vulgaris; Phaeoisariopsis griseola; Uromyces appendiculatus; fungicide; grain yield